2011
DOI: 10.1007/s12013-011-9211-7
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of Different Endovascular Methods for Treatment of Refractory Budd–Chiari Syndrome

Abstract: The study's objective was to evaluate the applicability of different endovascular methods for treatment of refractory type of Budd-Chiari syndrome (BCS) under specific scenarios frequently encountered in patients. The treatment methods were evaluated in 197 patients with the following four types of refractory BCS: lesions of the inferior vena cava (IVC) including a special shape diaphragm (e.g., a knife- or a vertically shaped diaphragm, etc.), occlusion of the long segment of IVC, IVC obstruction combined wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 9 publications
2
17
0
Order By: Relevance
“…The average diameter of AHV stems in our patients was 8.0 ± 2.6 mm, which is also comparable with that (7.3 ± 3.9 mm) in the MRA study [12]. The purpose of management of BCS is improving patients' symptoms and liver function [5][6][7][8]. Most previous studies have demonstrated that HV recanalization is suitable for patients with short segmental obstruction of HV [7][8][9].…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…The average diameter of AHV stems in our patients was 8.0 ± 2.6 mm, which is also comparable with that (7.3 ± 3.9 mm) in the MRA study [12]. The purpose of management of BCS is improving patients' symptoms and liver function [5][6][7][8]. Most previous studies have demonstrated that HV recanalization is suitable for patients with short segmental obstruction of HV [7][8][9].…”
Section: Discussionsupporting
confidence: 85%
“…The purpose of management of BCS is improving patients' symptoms and liver function [5][6][7][8]. Most previous studies have demonstrated that HV recanalization is suitable for patients with short segmental obstruction of HV [7][8][9]. However, HV recanalization is difficult with a high failure rate in patients with long segmental obstruction or diffuse obstruction of HV [7][8][9].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations